Effect of an Electronic Health Record Transition on the Provision of Recommended Well Child Services in Pediatric Primary Care Practices. (February 2020) - Binney, Geoffrey; Cole-Poklewski, Tamalie; Roomian, Tamar; Trudell, Emily K.; Hatoun, Jonathan; O'Donnell, Heather; Vernacchio, Louis
We sought to determine the effect of transitioning between electronic health record (EHR) systems on the quality of preventive care in a large pediatric primary care network. To study this, we performed a retrospective chart analysis of 42 primary care practices from the Pediatric Physicians' Organization at Children's who transitioned EHRs. We reviewed 24 random encounters per week distributed evenly across 6 age categories before, during, and after a transition period. We reviewed encounter documentation for age-appropriate well child services, per American Academy of Pediatrics/Bright Futures guidelines. Logistic regression and statistical process control analysis were used. In the pretransition period, 84.5% of all recommended elements were documented versus 86.4% posttransition ( P = .04). Documentation of age-appropriate anticipatory guidance showed significant positive change (69.0% to 80.2%, P = .005), but it was the only subdomain with a statistically significant increase. These increases suggest that EHR transitions have the opportunity to affect the delivery of preventive care.